Effective Thermal Insulation The Operative Factor of a Passive Building Model - Almusaed, Amjad (IntechOpen, 2012)
This book has been written to present elementary practical and efficient applications in saving energy concept, as well as propose a solitary action for this category of topics. The book aims to illustrate various methods in treatment the concept of thermal insulation such as processes and the attempt to build an efficient passive building model.